An Experimental Study to Demonstrate the Effect of Alumina Nanoparticles and Synthetic Fibers on Oil Well Cement Class G - Saadoon, Ayoob M.; Al-Haleem, Ayad A.; Al-Yasri, Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
In the drilling and production operations, the effectiveness of cementing jobs is crucial for efficient progress. The compressive strength of oil well cement is a key characteristic that reflects its ability to withstand forceful conditions over time. This study evaluates and improves the compressive strength and thickening time of Iraqi oil well cement class G from Babylon cement factory using two types of additives (Nano Alumina and Synthetic Fiber) to comply with the American Petroleum Institute (API) specifications. The additives were used in different proportions, and a set of samples was prepared under different conditions. Compressive strength and thickening time measurements were taken under different conditions. The amounts of Nano Alumina (0.5%, 1%, and 1.5% by weight of cement (BWOC)) were selected with synthetic fiber (0.5 g, 1 g, and 1.5 g, respectively). The results show a significant improvement in compressive strength, with all values meeting the API requirements, and a decrease in the thickening time of Iraqi oil well cement, depending on the proportions of additives. The most significant improvement in compressive strength was achieved in the sample containing 1.5% Nano Alumina by weight of cement (BWOC) and 1.5 g Synthetic Fiber (Barolift), where the compressive strength increased by 40.7% and 33.8% at a temperature of 38 °C and 60 °C, respectively, while the thickening time decreased by 26.53% at this ratio of additives. The results demonstrate the feasibility of using these additives to enhance the performance of Iraqi oil well cement, expanding its potential application in Iraqi oil fields.